Efektifitas Metode Eksplorasi Konsep dalam Studio Perancangan Arsitektur Tematik Bagi Mahasiswa Studi Kasus: Universitas Merdeka Surabaya - Vijar Galax Putra Jagat Paryoko (ARSITEKTURA, 2019)
Study in thematic architectural design studios for undergraduate students requires the participants to be able to convey the image and the meaning behind it through architectural design. Skills on comprehensive design process and utilization of appropriate methods are determine the success on implementing architectural meanings through design theme. This research aims to find exploring ideas methods which are effective be used to for generate thematic concepts. The research uses qualitative strategies to examine the processes and products outcomes of studio participant’s study that are controlled through design theories which studied by them. It was concluded that analogic design method is an effective category to be used, both analogy by sources inside architecture field and outside. Both analogy of form, meaning, and image. In addition, the level of diversity and depth understanding of design methods also influence the success of architectural design by themes.